Backstepping based intelligent control of tractor-trailer mobile manipulators with wheel slip consideration - Soni; Kumar, Naveen (ISA transactions, 2024)
In this research, a new hybrid backstepping control strategy based on a neural network is proposed for tractor-trailer mobile manipulators in the presence of unknown wheel slippage and disturbances. To minimize the negative impacts of wheel slippage, the desired velocities of the tractor’s wheels are computed with a proposed kinematic control model with an adaptive term. As the system’s dynamical model contains unavoidable uncertainties, model-based backstepping control technique is unable to effectively manage these systems. Hence, the proposed controller blends a radial basis function neural network with the merits of a dynamical model-based backstepping approach. The neural networks are employed to approximate the non-linear unknown smooth function. To minimize the impact of external disturbances, and network reconstruction error an adaptive term is added to the control law. The Lyapunov theorem and Barbalat’s lemma are employed to guarantee the stability of the control method. The tracking error is shown to be bounded and to rapidly converge to zero with the proposed method. To demonstrate the efficacy and validity of the control mechanism, comparison simulation results are presented. •A hybrid controller is proposed for tractor-trailer systems with wheel slippage.•By putting forward a kinematic control law, the desired velocities are calculated.•At the dynamical level, RBFNN is used to approximate the uncertainties of the system.•The stability of the system is analyzed with Lyapunov theory and Barbalat’s Lemma.•The proposed control scheme is verified through simulation studies.